High triglyceride-glucose index in patients with diabetes mellitus is associated with an increased likelihood of nephropathy development: evidence from a meta-analysis among Asian population - Raphael Enrique Tiongco; Neil David Cayanan; Michael John Dominguez; Kyll Geonzon; Julie Ann Mercado; Maria Ruth Pineda-Cortel (The Egyptian Journal of Internal Medicine)
Abstract Introduction In recent years, the triglyceride-glucose (TyG) index, which is associated with insulin resistance and kidney dysfunction, has emerged as a promising and accessible biomarker for the diagnosis and prognosis of diabetic nephropathy (DN). In this study, we examined the association of TyG in DN by meta-analyzing relevant literature. Methods Literature search and serial omissions of articles yielded eight studies for inclusion in the meta-analysis. Relevant data were extracted from the included studies and were subjected to analysis using Review Manager 5.4. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were computed from the included studies. Subgroup analysis was also performed to control for the participant's ethnicity. Results Out of the 1,229 resulting studies, only eight were included based on the set inclusion criteria. The overall pooled outcomes resulted in significant and homogeneous findings favoring the development of DN among patients with diabetes due to high levels of TyG. The findings of the present study are supported by the homogeneous outcomes, stability of findings, and high significance level. Conclusion Overall, our results show that high levels of TyG are associated with DN development, especially among the Asian population with diabetes. However, further longitudinal and multi-ethnic studies are needed to verify these claims.